Characterizing Grocery Store COVID-19 Controls in the Pacific Northwest - Chan, Allen (My University, 2021)
University of WashingtonAbstract Characterizing Grocery Store COVID-19 Controls in the Pacific Northwest Allen Chan Chair of Supervisory Committee:Marissa Baker Department of Environmental and Occupational Health Sciences Objectives: To characterize grocery store health and safety controls implemented during the COVID-19 pandemic across stores in different cities, areas of differing levels of income, and types of stores.Methods: This longitudinal, observational study of 16 stores between Seattle, WA (n=9) and Portland, OR (n=7) was conducted from May 2020 to January 2021. Stores were visited monthly and observations of controls were recorded using a standardized checklist in REDCap. Descriptive analyses were conducted to determine the proportion of stores with a certain control. Results: Controls like mask requirements and plexiglass screens at checkout were most common and consistent across stores and over the study period. There were no clear trends in the implementation of controls among grocery stores of different cities, in areas with differing income levels, and of different chains. Conclusions: Of the controls observed, mask requirements and plexiglass screens were most common. Specific rules could ensure quick and consistent adoption of controls (e.g., mask mandate). Additionally, low maintenance, less resource intensive controls (e.g., screens) may be easier for stores to implement.
Thesis (Master's)--University of Washington, 2021
Keywords: COVID-19; Grocery stores; SARS-CoV-2; Workplace controls; Occupational safety; Public health; Environmental health